IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING WORD WALL MEDIA AT SMP NEGERI 3 TONDANOIMPROVING STUDENTS’ VOCABULARY MASTERY BY USING WORD WALL MEDIA AT SMP NEGERI 3 TONDANO - Makalalag, Mifta Huljanah; Muntuuntu, Meity; Andries, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
In carrying out the learning process, teachers can choose and use several learning media that are appropriate to the characteristics of students and subject matter. The aims of this research was to find out the improvement of the students’ vocabulary mastery by using Word Wall media of 7th grade students at SMP Negeri 3 Tondano consisted of 33 students as sample. Data collection technique was in the form of Pre-test and Post-test with the quantitative approach. Treatment is done after Pre-test. The test was in the form of multiple choice test and matching test. The result of this research showed that students’ English vocabulary mastery sigificantly improved by using Word Wall media, it can be seen from the mean score of Pre-test and Post-test, where the mean score of Post-test (81.81) was higher than the mean score of Pre-test (65.45). It means Word Wall media could improved the students’ vocabulary mastery